ALEXEY LOSEV: LIFE AND DESTINY OF A PHILOSOPHER - Lyudmila B. Logunova; Yuriy Yu. Petrunin (Высшее образование в России)
This article is an attempt to create a portrait of Alexey Losev in the interior of the domestic history of the twentieth century. In this aspect, the fate of the philosopher appears as a personification of a contemporary historical era that allows us to understand history not as an objective impersonal process, but as a drama of lives and ideas. Research method is the interpretation of philosophical and literary texts (prose and poetry), diaries, and memoirs of people who knew A.F. Losev.